Mapping the scientific output of the Costal Studies Program (PEC) of the Museu Paraense Emílio Goeldi, Belém, Pará, Brazil, as a contribution to coastal ecosystem services - Borges, Heloísa Vargas; Mendes, Amílcar Carvalho; Miranda, Artur Gustavo Oliveira de; Harada, Ana Yoshi (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The Amazon coastal zone comprises an area of 9,000 km², located between the Oiapoque River in Amapá and São Marco Bay, Maranhão, Brazil. Several environments characterize the area, such as beaches, tidal plains, salty and freshwater marshes, estuaries, mangroves, lowland rainforest, tropical forests, lakes, lagoons, islands, rivers, deltas, dunes. This essay using scientific articles published from 1997 to 2015 by Museu Paraense Emílio Goeldi (MPEG) researchers tries to map the scientific output of the Coastal Studies Program (PEC) that completes 20 years of existence in 2017. The map produced from this bibliographical survey offers data on zoology, botany, geology, anthropology, archeology, ecological and multidisciplinary studies as a contribution to Marine and Coastal Ecosystems Services (MCES).